Pelatihan Pembuatan Label Usaha untuk Meningkatkan Pemasaran UMKM di Kabupaten Lombok Utara - Gozin Najah Rusyada; Baiq Rabiatul Adawiyah Kartika Wulan; Risyaf Kudus Pranasa; I Nyoman Switrayana; Logi Mulawarman (Insan Kreasi Media, 2023)
It is necessary to prioritize the roles of all parties in order to activate the marketing of UMKM after the COVID-19 pandemic, including academics. Activities that can be carried out by stakeholders from academia are to provide knowledge and guidance to business actors, and one of them is training in labeling to improve the marketing of UMKM players. This activity is carried out in the form of dedication with the methods of implementation, such as preparation, training, and evaluation. The results of the service show that training activities for making business labels to improve MSME marketing in the North Lombok district can increase the knowledge of training participants regarding product business labels, including (1) the rules for making labels, (2) the function of labels to improve marketing, and (3) the steps for making labels using CorelDraw and Canva software.